Death Anxiety and Empathy Among Male and Female Medical Students - Žydrūnė Kaklauskaitė; Dalia Antinienė (Lithuanian Sports University, 2018)
Background. Research reveals that death anxiety affects physicians' quality of work when he/she faces a patient suffering from a fatal disease (Field & Howells, 1988, Thiemann, Quince, Benson, Wood, & Barclay, 2015), while empathy leads to medical decision making and a better patient's healing process (Lor, Truong, Ip, & Barnett, 2015; Chen, Kiersma, Yehle, & Plake, 2015). The aim of this study was to investigate the relationship between death anxiety and empathy by gender among students of the medicine program in the Lithuanian University of Health Sciences. Methods.  The  study  involved  233  students  of  the  medical  program  from  the  Faculty  of  Medicine  in  the Lithuanian University of Health Sciences. The sample consisted of 167 women (71.1%) and 56 men (24%), 10 participants have not specified their gender (4.9%). A questionnaire designed for the study consisted of demographic questions, Interpersonal Reactivity Index (IRI) (Davis, 1980) and Revised Collet-Lester Fear of Death and Dying Scale (Lester, 1990). Results. Medical students that show higher than others anxiety about death of self 1 , dying of self 2 , death of others 3  and dying of others 4  also show greater personal distress (r = .211 1 ; r = .217 2 ; r = .248 3 ; r = .219 4 ), empathetic concern (r = .205 1 ; r = .241 2 ; r = .246 3 ; r = .136 4 ), emotional (r = .27 1 ; r = .294 2 ; r = .319 3 ; r = .236 4 ) and overall   r = .237 1 ; r = .262 2 ; r = .254 3 ; r = .227 4 ) empathy and also had better fantasy (r = .149 1 ; r = .173 2 ; r = .149 3 ; r = .184 4 ) than others. Weak correlation in men sample was between death anxiety subscales and empathetic concern (r = .532 1 ; r = .279 2 ; r = .3 3 ; r = .306 4 ), emotional (r = .48 1 ; r = .364 2 ; r = .373 3 ; r = .458 4 ) and overall (r = .369 1 ; r = .399 2 ;   r = .32 3 ; r = .453 4 ) empathy. Very weak correlation in women sample was found between emotional empathy and death of self (r = .164), dying of self (r = .188) and death of others (r = .206) anxiety. Personal distress subscale in women sample was associated with death of self (r = .186) and death of others (r = .179) anxiety. Conclusion. It was found that medical students showing greater personal distress, empathetic concern, fantasy, emotional and overall empathy have a stronger sense of death anxiety. Correlations between death anxiety and empathy  found  in  men  sample  were  specified  as  weak,  meanwhile  correlations  found  in  women  sample  were specified as very weak. Keywords: cognitive empathy, emotional empathy, fear of death.